The Effectiveness Of English Songs In Improving Students’ Listening Skill At The Ten Grade Students Of SMAN 2 Majene - Masrawati (Journal of Research Education and English Teaching, 2025)
This research is to see the effect of popular songs in improving students’ listening skill. The sample was 14 of the seventh year students of SMA N 2 Majene. The sample class is ten grade. The effect of popular songs can be seen from students’ listening scores test. The writer used a quantitative method design as the research methodology with a purposive sampling technique. The research instrument was listening cloze test. This study analysed the use of songs to help improve vocabulary mastery in listening class. The major concern was about the description of song’s implementation in the classroom and the extent to which the use of songs could help the students improve their vocabulary mastery in listening class. From the result it was obtained that the score of students increased. From the class pre-test treatment that consist of 14 students have been happen change score in the post-test treatment there were 15% classified excellence, 30% of students classified above of good, 35% classified that good, and the under category 20% of them. There is a change that happen to the students after applied this method. From the percentage degree significant change happen on post-test treatment given a positive effect. The last, this study is expected to bring contribution as the alternative technique to enhance teaching vocabulary in listening class as well as to develop teacher’s creativity to make it work.